Justice, Context, and Violence: Law Enforcement Officers on Why They Torture. Issue 4 (December 2014) - Wahl, Rachel
<x xml:space="preserve">Abstract</x> How do police explain their support for torture? Findings from 12 months of fieldwork with police in India complicate previous researchers' claims that violence workers tend to morally disengage and blame circumstances for their actions. The officers in this study engage in moral reflection on torture, drawing on their beliefs about human nature and justice to explain their support for it. They admit that they use torture more widely than their own conceptions of justice allow, but see this as an imperfect implementation of their principles rather than as a violation of them. Previous research on the spread of human rights norms has focused on how these norms can be adapted to the local beliefs that support them, rather than on understanding the beliefs that conflict with human rights. I argue that illuminating the self‐understanding of state actors who support or engage in torture is crucial to building theory on why such violence occurs, as well as to designing interventions to prevent it.